2008
DOI: 10.1523/jneurosci.4121-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Light Adaptation in Salamander L-Cone Photoreceptors

Abstract: The responses of individual salamander L-cones to light steps of moderate intensity (bleaching 0.3-3% of the total photopigment) and duration (between 5 and 90 s) were recorded using suction electrodes. Light initially suppressed the circulating current, which partially recovered or "sagged" over several seconds. The sensitivity of the cone to dim flashes decreased rapidly after light onset and approached a minimum within 500 ms. Background light did not affect the rising phase of the dim flash response, a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 37 publications
3
28
2
Order By: Relevance
“…4 E 1 ), reminiscent of the current undershoot reported for primate cones (Baylor et al, 1987). This undershoot was proposed to be related to delayed activation of GCs (Soo et al, 2008) by GC activating protein 2 (GCAP2), which, during light adaptation, regulates GC activity to restore high resting [Ca 2ϩ ] levels (Mendez et al, 2001). An alternative explanation is VGCC-dependent spiking, which has been reported for human rods (Kawai et al, 2001) and cones (Schnapf et al, 1990).…”
Section: Light-evoked Camentioning
confidence: 91%
“…4 E 1 ), reminiscent of the current undershoot reported for primate cones (Baylor et al, 1987). This undershoot was proposed to be related to delayed activation of GCs (Soo et al, 2008) by GC activating protein 2 (GCAP2), which, during light adaptation, regulates GC activity to restore high resting [Ca 2ϩ ] levels (Mendez et al, 2001). An alternative explanation is VGCC-dependent spiking, which has been reported for human rods (Kawai et al, 2001) and cones (Schnapf et al, 1990).…”
Section: Light-evoked Camentioning
confidence: 91%
“…Tranchina showed that both WT and GCAPs−/− mouse rod response waveform and sensitivity could be modeled by assuming that light directly regulates the decay of PDE6. Unlike Soo et al [46], however, Tranchina found that modulation of only light-activated PDE6 could not explain the responses of WT and GCAPs−/− rods; the decay of both spontaneous and light-activated PDE6 had to be accelerated to produce model calculations that replicated actual recordings.…”
Section: What Is Missing?mentioning
confidence: 83%
“…We can tell that this is so by comparing the open circles to the curve of large dashes, which is the prediction of a simple expression that assumes that all of adaptation has been eliminated and that the rod is simply summing responses of single photons with no active mechanism of sensitivity regulation [12]. The open circles should also be compared to the dotted curve of Chen et al [14], from a model developed by Dan Tranchina based on earlier models of Hamer and collaborators [44] and of Soo et al [46]. The Tranchina model successfully predicts Weber-Fechner-like adaptation for WT rods [14], but the dotted curve in Fig.…”
Section: Mouse Mutant Lines and Genetic Deletion Of Ca2+ Regulation Omentioning
confidence: 99%
See 1 more Smart Citation
“…. The initial rise of the photoreceptor response remains rather constant under moderate adaptation (Thomas and Lamb, 1999;Friedburg et al, 2001;Nymark et al, 2005) and is similar in cones as well (Soo et al, 2008). Because visual latency (or reaction time) is basically determined by the rising edge of responses (Donner, 1989b), delaying recovery kinetics alone need not slow down reactions to moving contrast borders.…”
Section: Temporal Integration Versus Resolution At Different Levels Imentioning
confidence: 99%